An unusual tumor of the vagina - Archana; Saritha Shamsunder; Amit Yadav; Sunita Malik (Indian Journal of Medical and Paediatric Oncology)
A 28-year-old female came with complaints of swelling in the perineal area; examination revealed a nontender and fixed mass of approximately 4 cm × 3 cm on the right vulvovaginal junction extending into the vaginal wall. Wide excision of the mass was performed; histopathological examination revealed features suggestive of Merkel cell carcinoma of vagina.